2016
DOI: 10.1007/s00264-016-3254-8
|View full text |Cite
|
Sign up to set email alerts
|

Early aseptic loosening of cementless monoblock acetabular components

Abstract: Purpose: Early aseptic loosening of cementless monoblock acetabular component is a rare complication of total hip arthroplasty (THA) and hip resurfacing arthroplasty (HRA). The purpose of this study was to evaluate the incidence and risk factors for early aseptic loosening of the cementless monoblock acetabular components.Methods: This retrospective analysis consisted of 4043 cementless hip devices (3209 THAs and 834 HRAs). We identified forty-one patients with early aseptic loosening of the acetabular compone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…The association between aseptic failure and implant position has been investigated in a limited fashion. Miyakawa et al 29 demonstrated that both gritbasted and hydroxyapatite-coated cups had a higher chance of aseptic failure if implanted in an excessively horizontal position, while Miettinen et al 30 noted that components placed more vertically and less anteverted had higher tendencies to loosen in the short term. Taken together, these findings could suggest that malposition limits boneimplant contact, and the resulting shear forces prevent osseointegration and produce radiolucencies.…”
Section: Discussionmentioning
confidence: 99%
“…The association between aseptic failure and implant position has been investigated in a limited fashion. Miyakawa et al 29 demonstrated that both gritbasted and hydroxyapatite-coated cups had a higher chance of aseptic failure if implanted in an excessively horizontal position, while Miettinen et al 30 noted that components placed more vertically and less anteverted had higher tendencies to loosen in the short term. Taken together, these findings could suggest that malposition limits boneimplant contact, and the resulting shear forces prevent osseointegration and produce radiolucencies.…”
Section: Discussionmentioning
confidence: 99%
“…For smaller defects, good results could be achieved with standard implants or jumbo cups that give good stability and osteointegration but require a significant bone contact. In case of osteolysis of both the anterior and posterior column, this is hard to obtain and the primary stability often results impaired; moreover, a suboptimal positioning of the cup rise the risk for an early loosening [6,7,15,16,17,18]. Cages and rings have the peculiarity of bridging the defect respectively with or without osteointegrative qualities and can be positioned independently from the final cup, which is usually cemented into the device after stability is achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Only the usage of self-locking cups was identified as relevant risk factor; however, gender did not influence the rate of periprosthetic fractures [ 9 ]. Sharkey et al suggested that oversizing of the cup may be associated with an increased rate of periprosthetic acetabular fractures [ 22 ] whereas undersizing may be associated with early loosening as a result of insufficient press-fit [ 18 ]. Additional benefits of accurate preoperative planning include shortened surgical time, and reduced complications with equipment and an improved reconstruction of individual joint geometry [ 11 ].…”
Section: Introductionmentioning
confidence: 99%